Graph-Based Algorithms for Optimizing Data Flow in Distributed Cloud Architectures (International Journal of Scientific Research and Management (IJSRM), 2022)
Improving data communication in DCAs can help correspondingly improve the system’s intrinsic performance, scalability, and dependability. With the complexity of cloud environments ever rising, efficient data messaging across multiple nodes is sometimes a significant issue. Thus, graph-based algorithms, derived from graph theory, provide ferm methods of solving these issues as data flow is presented in the form of graphs based on interconnected nodes and edges. This paper aims to highlight how different graph base algorithms including shortest path algorithms, flow optimization as well as load balancing algorithms can be used to enhance the data flow in distributed cloud systems. Using such algorithms can help the cloud providers optimize allocation, reduce response time, build in redundancy, and increase network utilization. The paper also points out the drawbacks connected with these algorithms, such as scalability and computational complexity. They also indicate future research areas, such as applying more advanced features from machine learning and the employment of quantum computing to enhance the graph-based optimization approach. Overall, this work offers insight into the applicability of the graph theory on flows to achieve data flow effectiveness in enhancing the performance of distributed cloud architecture.